The Textual Structure of the Jessica-Mirna Judicial Text: An Forensic Linguistic Approach - Nidya Fitri; Ketut Artawa; Made Sri Satyawati; Sawirman (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
This current study, in which the forensic linguistic approach and the theory of textualgeneric structure were applied, focuses on the judicial text in which Jessica was the defendantand Mirna was the victim. The judicial text, in which Jessica was the defendant and Mirna wasthe victim, is a dialogical conversation containing the textual procedure referring to structure.The textual structure of the judicial text, in which Jessica was the defendant and Mirna was thevictim, is made up of three main phases; they are the textual structure of the opening, the textualstructure of the content and the textual structure of the closing. Each phase is made up of sub-phases. The qualitative descriptive method was employed in the study. The data were collectedthrough observation and recording, and were obtained from 17 audio-visual recordings, whichwere then transcribed into Indonesian. The findings of the study show that (1) the opening phasewas made up of the criminal trial phase, the interrogation phase of the defendant’s identity, theindictment reading phase by the general prosecutor ; (2) the content phase was made up of thequestion phase as to objection from the defendant (exception), the interrogation phase of thewitnesses and expert, namely their (a) identities, (b) oath taking, and (c) the testimony of thewitnesses and expert and the interrogation phase of the defendant; (3) the textual structure of theclosing was made up of the indictment reading phase by the prosecutor, the verdict readingphase, and the trial closing phase. The finding of the study shows the representation of thetextual structure as the textual procedural standard based on the judicial text used in the currentstudy.